Molecular and Antibiotic Resistance Study of Acinetobacterbaumannii Isolated From Different Sources - Abdulrahman, Zirak F.A. (Sulaimani Journal for Pure and Applied Sciences, 2016)
A total of thirty five Acinetobacterbaumanniii solates were identified from burn, wound, urine, and sputum samples among two hundred forty five patients admitted to Rizgary, Erbil Teaching, and West Emergency hospitals in Erbil city during the period of February 1, 2013to May 15, 2014. The isolateswere identified by colonial appearance, morphological characteristics, biochemical tests, VITEK 2 system, and Polymerase Chain Reaction (PCR) technique, through amplification of blaOXA-51. The PCR product on gel electrophoresis was 353bp which confirm that the isolates were Acinetobacterbaumannii. A. baumanniitested for antibiotics susceptibility test using agar diffusion method and the results showed that 35 (100%), 35 (100%), 25 (71.42%), 22 (62.85%), 19 (54.28%), 16 (45.71%), 14(40%),8 (22.85),7 (20),and 3 (8.57) were resistant to Vancomycin, Penicillin, Cefotaxime, Ceftriaxone, Erythromycin, Doxycycline, Streptomycin, Gentamycin, Imipenem, and Cefazolinrespectively.All isolates of A. baumannii were susceptible to ciprofloxacin. The isolates were screened for the presence of carbapenem resistance–associated outer membrane protein gene (carO gene) and the results shows that 18 (51.42%) isolates were positive for the (carO gene) using polymerase chain reaction (PCR) assay.To control the antibiotic resistance of the tested Acinetobacterbaumanniiisolates, curing of plasmid DNA was conducted using ethidium bromide. One of the most resistance isolate was chosen for this purpose (A33) then treated with Ethidium bromide at concentration (50, 75,100,125,150,and 175μg/ml). The results revealed that the genes encoded resistance for Imipenem, Vancomycin, penicillin,and doxycycline were cured from A33 and the percentage of curing was (36.3%) and the best concentration was 125 μg/ml.
Keywords: Acinetobacterbaumannii; Antibiotics susceptibility,carOgene,andPlasmid curing